Mindfulness training for psychological stress in family caregivers of persons with dementia: a systematic review and meta-analysis of randomized controlled trials - Liu Z (Dove Medical Press, 2017)
Zheng Liu,1 Qian-lin Chen,1 Yu-ying Sun2 1Department of Psychiatry, The Chinese University of Hong Kong, Tai Po Hospital, Hong Kong SAR, China; 2The Jockey Club School of Public Health and Primary Care, Faculty of Medicine, The Chinese University of Hong Kong, Hong Kong SAR, China Abstract: Caring for a relative with dementia is extremely challenging; conventional interventions may not be highly effective or easily available on some occasions. This study aimed to explore the efficacy of mindfulness training in improving stress-related outcomes in family caregivers of people with dementia using a meta-analytic review. We searched randomized controlled trials (RCT) through April 2017 from five electronic databases, and assessed the risk of bias using the Cochrane Collaboration tool. Seven RCTs were included in our review. Mindfulness interventions showed significant effects of improvement in depression (standardized mean difference: -0.58, [95% CI: -0.79 to -0.37]), perceived stress (-0.33, [-0.57 to -0.10]), and mental health-related quality of life (0.38 [0.14 to 0.63]) at 8 weeks post-treatment. Pooled evidence did not show a significant advantage of mindfulness training compared with control conditions in the alleviation of caregiver burden or anxiety. Future large-scale and rigorously designed trials are needed to confirm our findings. Clinicians may consider the mindfulness program as a promising alternative to conventional interventions. Keywords: dementia caregivers, mindfulness, randomized controlled trials, meta-analysis